Routledge international encyclopedia of queer culture - Gerstner, David A. (Routledge, 2006)
The Routledge International Encyclopedia of Queer Culture covers gay, lesbian, bisexual, transgender and queer (GLBTQ) life and culture post-1945, with a strong international approach to the subject.The scope of the work is extremely comprehensive, with entries falling into the broad categories of Dance, Education, Film, Health, Homophobia, the Internet, Literature, Music, Performance, and Politics. Slang is also covered. The international contributors come from a wide array of backgrounds: scholars, journalists, artists, doctors, scientists, lawyers, activists, and an enormous range of ideologies and points of view are represented. Major entries provide in-depth information and consider the intellectual and cultural implications of their subjects in a global context. Information is completely up-to-date, including full coverage and analysis of such current or ongoing issues as same-sex marriage/civil union and the international AIDS epidemic. Additionally, there are important appendices covering international sodomy laws and archival institutions, which will be of great value to researchers. The Encyclopedia is fully cross-referenced and many entries carry a bibliography. Where possible internet references have been given and there is a full index.The combination of its wide scope, determined international coverage and appendices make the Routledge International Encyclopedia of Queer Culture a uniquely ambitious work and an extremely rich source of information. It is a priority addition for all libraries serving scholars and students with an interest in GLBTQ culture, history and politics across the disciplines.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; incontournable; outils; ouvrages de références; queer; ressource en ligne; thématiques

No margins: Writing Canadian fiction in lesbian - Lake, Catherine; Holtz, Nairne (Insomniac Press, 2006)
Elegant tomboys, academic femmes, small town kisses, and international dykes; road trip encounters and scenes from a straight bar; questions arising from an in-between culture; the music of travel and hotel room orgasms. Crossing race, culture, and gender constraints, No Margins leads the reader through the lushness of lesbian life and the vastness of Canadian experience.No Margins is a stellar short fiction collection featuring fifteen of Canada's finest contemporary writers, all of whom include lesbian identity as a piece of their selves and their work. These highly acclaimed authors were selected to convey the places we currently inhabit and the future we are forging. The contributors have included notes to accompany their work, thus sharing the creative process and speaking on the politics of lesbian writing. No Margins is an unprecedented anthology, reflecting an esteemed gathering of women who are currently shaping Canadian literature.Featuring the work of: Luanne Armstrong • Dionne Brand • Nicole Brossard • Emma Donoghue • Marion Douglas • Anne Fleming • Jane Eaton Hamilton • Lydia Kwa • Larissa Lai • Ann-Marie MacDonald • Daphne Marlatt • Shani Mootoo • Elizabeth Ruth • Karen X. Tulchinsky • Marnie Woodrow
https://www.deslibris.ca/ID/440108
Keywords: amériques; anthologie; canada; fiction; littérature; outils; ouvrages de références; personnes lesbiennes; ressource en ligne; régions géographiques

Travestissement féminin et liberté(s) - Leduc, Guyonne (L'Harmattan, 2006)
Ce livre nous invite à découvrir les nombreuses facettes du travestissement féminin dans la culture occidentale des XVIè-XXè siècles. Pourquoi se travestir ? Par amour, par patriotisme, pour fuir des violences domestiques, pour vivre une aventure... Les motifs sont multiples. Travestissement, et non femmes travesties : l'ouvrage s'intéresse avant tout au formidable révélateur social, culturel et esthétique qu'est le travestissement. Il met à nu le mécanisme de la construction des genres ; il dévoile l'ordre sexuel qu'il défie.
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; genre; har4600; histoire et politique; identités LGBTQIA2+; outils; premier cycle; rapports sociaux de sexe; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; travestissement; études littéraires